Human capital, economic growth, and regional inequality in China - Belton M. Fleisher; Haizheng Li; Min Qiang Zhao (Institute for the Study of Labor (IZA), 2008)
We study the dispersion in rates of provincial economic- and TFP growth in China. Our results show that regional growth patterns can be understood as a function of several interrelated factors, which include investment in physical capital, human capital, and infrastructure capital; the infusion of new technology and its regional spread; and market reforms, with a major step forward occurring following Deng Xiaoping's South Trip in 1992. We find that FDI had much larger effect on TFP growth before 1994 than after, and we attribute this to emergence of other channels of technology transfer when marketization accelerated. We find that human capital positively affects output per worker and productivity growth. In particular, in terms of its direct contribution to production, educated labor has a much higher marginal product. Moreover, we estimate a positive, direct effect of human capital on TFP growth. This direct effect is hypothesized to come from domestic innovation activities. The estimated spillover effect of human capital on TFP growth is positive and statistically significant, which is very robust to model specifications and estimation methods. The spillover effect appears to be much stronger before 1994. We conduct cost-benefit analysis and a policy experiment, in which we project the impact of increases in human capital and infrastructure capital on regional inequality. We conclude that investing in human capital will be an effective policy to reduce regional gaps in China as well as an efficient means to promote economic growth.
urn:nbn:de:101:1-2008071112
Keywords: O15; 330; China; TFP growth; economic growth; human capital; infrastructure; Regionales Wachstum; Regionale Disparität; Produktivität; Wirtschaftswachstum; Bildungsinvestition; Direktinvestition; Infrastrukturinvestition; Spillover-Effekt; China